Efektivitas Model Pembelajaran Tematik Terpadu Berbasis Lingkungan Terhadap Minat Belajar IPS Siswa Kelas IV Sekolah Dasar - Meilia Prehartanti; Rendi Atnanto; Ade Ismail Fahmi; Mia Audina Musyadad; Diah Widiawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Social Studies learning in elementary schools often faces challenges in the form of low student interest in learning, especially when the material is presented in an abstract and less contextual manner. To address this issue, this study aims to describe the effectiveness of an integrated thematic learning model based on the environment in increasing interest in learning social studies at fourth-grade students of SDN Palumbonsari II, East Karawang District. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through observation, in-depth interviews, and documentation, with research subjects consisting of fourth-grade teachers and students. The results of the study indicate that the implementation of an integrated thematic model based on the environment can significantly increase student interest in learning. This is evident from the increase in students' active participation in the learning process, enthusiasm in extracurricular activities, and their ability to connect social studies material with the surrounding reality. Learning activities that utilize the environment as a learning resource also successfully create a fun and meaningful learning atmosphere. The implications of this study emphasize the importance of the role of teachers in designing contextual-based learning that is integrated with the local environment, especially in social studies subjects that are rich in social life values.